(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Our main purpose is to introduce the concept of quasi θ(τ_1,τ_2)-continuous functions. Furthermore, several characterizations and some properties of quasi θ(τ_1,τ_2)-continuous functions are investigated.